Updated ACMG/AMP specifications for variant interpretation and gene curations from the ClinGen RASopathy expert panels - Emma H. Wilcox; Ryan F. Webb; Kezang C. Tshering; Madeline Y. Hughes; Hélène Cavé; Marina T. DiStefano; Hannah Dziadzio; Kate Garber; Bruce D. Gelb; Karen W. Gripp; Shoji Ichikawa; Jennifer A. Lee; et al. (Genetics in Medicine Open)
Purpose: The ClinGen RASopathy (RAS) Variant Curation Expert Panel (VCEP) previously established RASopathy specifications to the American College of Medical Genetics and Genomics (ACMG) and Association of Molecular Pathology (AMP) variant classification framework for more consistent and accurate variant classification. Advances in the understanding of RASopathies and new clinical genetic testing algorithms required updated specifications. Methods: The RAS Gene Curation Expert Panel recurated 6 gene-disease relationships, and the RAS VCEP evaluated the previous specifications to develop updated RASopathy specifications for the ACMG/AMP framework. The performance of these updated specifications was tested by reassessing 59 previously classified variants and 88 new pilot variants. Results: Five gene-disease relationships were upgraded to Definitive, whereas 1 was upgraded to Moderate. Updated specifications were applied to 11 ACMG/AMP criteria for disorders with a dominant inheritance, 3 criteria for recessive inheritance, and 4 criteria to align with recommendations from the ClinGen Sequence Variant Interpretation Working Group. Assessment of variants demonstrated no major shifts in classifications compared with previous RAS VCEP or ClinVar classifications. Conclusion: Updated RASopathy specifications improve the classification of variants associated with recessive disease and observed in exome/genome cases. Most of these specifications may also be used as a baseline for other rare Mendelian disorders.